Incidence of Methicillin-Resistant Staphylococcus Aureus (MRSA) Recovered from Patients with Urinary Tract Infections in Zakho City/ Kurdistan-Iraq - Hami, Iman A.; Ibrahim, Khalid S. (Science Journal of University of Zakho, 2023)
The prevalence of Staphylococcus aureus (S. aureus) among patients with urinary tract infections (UTIs) has become a significant cause of morbidity in all age groups. The aim of the current study was to identify S. aureus with methicillin-resistant S. aureus (MRSA). Moreover, it aimed to determine their antimicrobial susceptibility patterns and to detect the presence of the mecA, lukPV and icaA genes in isolated S. aureus among UTIs patients. A total of 402 urine samples were collected from patients diagnosed with UTIs aged (less than 80 years) at Zakho General Hospital in Zakho City, from August 2021 to March 2022. From these samples, a total of 37 (12.6%) S. aureus was identified and molecularly confirmed by the nuc gene. A high prevalence of MRSA 28 (75.7%) was identified from these isolates S. aureus by Oxacillin sensitive test and confirmed by mecA gene. Females were highly infected with UTIs than males, and most cases were in chronic condition and married. In addition, 18 (64.3%) and 21 (75%) of these isolates S. aureus were harbored luk-PV and icaA genes, respectively. There were widespread of antimicrobial resistance patterns for these bacteria. Isolated MRSA were highly sensitive to Imipenem. Interestingly, a significant positive correlation between mecA and both virulence marker genes (luk-PV and icaA) found in MRSA with UTIs. Conclusion, the data demonstrated, for the first time, alarming emergence of multidrug-resistant MRSA isolated from UTIs of community-acquired in Kurdistan Region-Iraq. Further studies are required in other cities to report whether or not MRSA is the cause of UTI patients in Iraqi Kurdistan.